Iran Diabetes Research Roadmap (IDRR) Study; Analysis of Diabetes Comorbidity Studies in Iran: A Review Article - Maryam PEIMANI; Zahra ABRISHAMI; Ensieh NASLI-ESFAHANI; Fatemeh BANDARIAN; Maryam GHODSI; Bagher LARIJANI (Tehran University of Medical Sciences, 2017)
Background: Most adult patients with diabetes have at least one comorbid chronic condition and approximately 40% have three or more. The purpose of this study was to investigate detailed characteristics of studies examining comorbidities of diabetes in Iran and to identify knowledge gaps in this field. Methods: All documents published by Iranian authors in national and international journals until 2015 were evaluated. A wide search was performed in PubMed, Web of Science, SCOPUS as well as SID, IranMedex and Magiran databases using proper keywords. The obtained documents were categorized into eleven subgroups of complications, comorbidities, management, psychiatry, nutrition, prevention, physical activity, genetics, basic sciences, education and gestational diabetes mellitus (GDM). Documents were categorized based on WHO and Australian National Health and Medical Research Council (NHMRC) classification, the study methodology and topic. Results: Overall, 311 documents were obtained. The trend of publications was ascending since 2000. About 70% of studies were about epidemiology and causes of comorbid disease and more than 90% of studies were clinical research. The design of the most studies was cross-sectional followed by case-control and randomized clinical trial. The most common subject of documents was related to endocrine (28.61%) followed by gastrointestinal (18.32%) and cardiovascular disease (14.14%). Conclusion: Epidemiological studies are the most common type of studies about diabetes comorbidity in Iran and cross-sectional design is the most frequent methodology used while there are few cohorts. There is no study about physiopathology and shared etiology and pathogenesis of these comorbidities and diabetes.